2020
DOI: 10.3390/md18060281
|View full text |Cite
|
Sign up to set email alerts
|

Pyrenosetin D, a New Pentacyclic Decalinoyltetramic Acid Derivative from the Algicolous Fungus Pyrenochaetopsis sp. FVE-087

Abstract: The fungal genus Pyrenochaetopsis is commonly found in soil, terrestrial, and marine environments, however, has received little attention as a source of bioactive secondary metabolites so far. In a recent work, we reported the isolation and characterization of three new anticancer decalinoyltetramic acid derivatives, pyrenosetins A–C, from the Baltic Fucus vesiculosus-derived endophytic fungus Pyrenochaetopsis sp. FVE-001. Herein we report a new pentacyclic decalinoylspirotetramic acid derivative, pyrenosetin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 44 publications
0
38
0
1
Order By: Relevance
“…Absolute configuration of compound 1 was determined using DFT prediction of optical rotation (OR) [ 17 , 18 , 19 ], using the same set of optimized conformers of model compound 1s ( Figure 2 ) that were used for NMR chemical shift prediction. In doing so, we made the reasonable assumption that the contribution to chiroptical properties, including molar rotation, of a remote non-chiral side chain is negligible [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Absolute configuration of compound 1 was determined using DFT prediction of optical rotation (OR) [ 17 , 18 , 19 ], using the same set of optimized conformers of model compound 1s ( Figure 2 ) that were used for NMR chemical shift prediction. In doing so, we made the reasonable assumption that the contribution to chiroptical properties, including molar rotation, of a remote non-chiral side chain is negligible [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…To determine the absolute configuration of metabolites, singlecrystal X-ray diffraction, NMR advanced Mosher's methods (for alcohols), Marfey's method (for aminoacids) are often used (Bhushan and Brückner, 2011;Cimmino et al, 2017). Computational approaches such as density functional theory (DFT) coupled with (i) NMR, (ii) chiroptical methods e.g., electronical circular dichroism (ECD), vibrational circular dichroism (VCD) spectroscopy and (iii) optical rotation are being successfully employed in identification of relative and absolute configuration of marine natural products (Merten et al, 2015;Batista et al, 2018;Menna et al, 2019;Wang and Hamann, 2019;Fan et al, 2020;Marcarino et al, 2020;Zhu and Sun, 2020). The elucidation of biosynthetic pathways from genomic sequence data is also used to support the absolute configuration assignment (Hu et al, 2018;Kim et al, 2020).…”
Section: Extraction Fractionation Isolation Structure Elucidationmentioning
confidence: 99%
“…The results revealed high activity against lymphoma cancer cells (U937) with IC 50 value at 500 µg/mL of β-cyclodextrin-Asparaginase nanobiocomposite. Golbabaie et al [11] used a crude L-Asparaginase enzyme mixed with cell viability to investigate the anti-cancer activity against K562 and HL60 cancer cell lines and lymphoblastic leukemia. The results revealed that the toxicity of the enzyme was determined with IC 50 values were calculated as 0.4 and 0.5 IU/mL for K562 and HL60 respectively.…”
Section: Smf MCDmentioning
confidence: 99%
“…The toxicity of L-asparaginase against K562 and HL60 cancer cell lines and L6 as normal cells was determined with IC 50 values were calculated as 0.4 and 0.5 IU/mL for K562 and HL60 respectively [11] Childhood leukemia L-Asparaginase with a dose of ≥ 6000 IU/sq m three times weekly.…”
Section: Cancer Type Preparation Activity Referencesmentioning
confidence: 99%
See 1 more Smart Citation